Chronic Organic Solvent Exposure Changes Visual Tracking in Men and Women - de Oliveira, Ana R.; Campos Neto, Armindo de Arruda; Bezerra de Medeiros, Paloma C.; de Andrade, Michael J. O.; dos Santos, Natanael A. (Frontiers in Neuroscience, 2017)
Organic solvents can change CNS sensory and motor function. Eye-movement analyses can be important tools when investigating the neurotoxic changes that result from chronic organic solvent exposure. The current research measured the eye-movement patterns of men and women with and without histories of chronic organic solvent exposure. A total of 44 volunteers between 18 and 41 years old participated in this study; 22 were men (11 exposed and 11 controls), and 22 were women (11 exposed and 11 controls). Eye movement was evaluated using a 250-Hz High-Speed Video Eye Tracker Toolbox (Cambridge Research Systems) via an image of a maze. Specific body indices of exposed and non-exposed men and women were measured with an Inbody 720 to determine whether the differences in eye-movement patterns were associated with body composition. The data were analyzed using IBM SPSS Statistics version 20.0.0. The results indicated that exposed adults showed significantly more fixations (t = 3.82; p = 0.001; r = 0.51) and longer fixations (t = 4.27; p = 0.001, r = 0.54) than their non-exposed counterparts. Comparisons within men (e.g., exposed and non-exposed) showed significant differences in the number of fixations (t =2.21; p = 0.04; r = 0.20) and duration of fixations (t = 3.29; p = 0.001; r = 0.35). The same was true for exposed versus non-exposed women, who showed significant differences in the number of fixations (t = 3.10; p = 0.001; r = 0.32) and fixation durations (t = 2.76; p = 0.01; r = 0.28). However, the results did not show significant differences between exposed women and men in the number and duration of fixations. No correlations were found between eye-movement pattern and body composition measures (p > 0.05). These results suggest that chronic organic solvent exposure affects eye movements, regardless of sex and body composition, and that eye tracking contributes to the investigation of the visual information processing disorders acquired by workers exposed to organic solvents.